Motor cortex electrical stimulation augments sprouting of the corticospinal tract and promotes recovery of motor function - Carmel, Jason B.; Martin, John H. (Frontiers in Integrative Neuroscience, 2014)
The corticospinal system—with its direct spinal pathway, the corticospinal tract (CST) – is the primary system for controlling voluntary movement. Our approach to CST repair after injury in mature animals was informed by our finding that activity drives establishment of connections with spinal cord circuits during postnatal development. After incomplete injury in maturity, spared CST circuits sprout, and partially restore lost function. Our approach harnesses activity to augment this injury-dependent CST sprouting and to promote function. Lesion of the medullary pyramid unilaterally eliminates all CST axons from one hemisphere and allows examination of CST sprouting from the unaffected hemisphere. We discovered that 10 days of electrical stimulation of either the spared CST or motor cortex induces CST axon sprouting that partially reconstructs the lost CST. Stimulation also leads to sprouting of the cortical projection to the magnocellular red nucleus, where the rubrospinal tract originates. Coordinated outgrowth of the CST and cortical projections to the red nucleus could support partial re-establishment of motor systems connections to the denervated spinal motor circuits. Stimulation restores skilled motor function in our animal model. Lesioned animals have a persistent forelimb deficit contralateral to pyramidotomy in the horizontal ladder task. Rats that received motor cortex stimulation either after acute or chronic injury showed a significant functional improvement that brought error rate to pre-lesion control levels. Reversible inactivation of the stimulated motor cortex reinstated the impairment demonstrating the importance of the stimulated system to recovery. Motor cortex electrical stimulation is an effective approach to promote spouting of spared CST axons. By optimizing activity-dependent sprouting in animals, we could have an approach that can be translated to the human for evaluation with minimal delay.